Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/his.13776
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial hyperplasia and the risk of coexistent cancer: WHO versus EIN criteria

Abstract: Endometrial hyperplasia (EH) is classified into benign and precancerous according to two different histomorphological systems: the World Health Organisation (WHO) system (based on the subjective evaluation of cytological atypia) and the endometrial intraepithelial neoplasia (EIN) system (based on a combination of several parameters that are assessable subjectively, or objectively through computerised analysis). The American College of Obstetricians and Gynecologists recommends use of the EIN system. Nonetheles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 37 publications
2
49
0
7
Order By: Relevance
“…We found that, for Bcl‐2 and PAX2, an aberrant expression correlated with EIN criteria of premalignancy better than with the WHO criteria, while no significant difference was found for PTEN . Furthermore, in another study we found that the EIN system was more sensitive, but less specific than the WHO one for the risk of cancer coexistent with EH . In these studies, we postulated that a major cause of the difference between WHO and EIN system may lie in the ‘complex non‐atypical EH’ category.…”
Section: Discussionmentioning
confidence: 86%
“…We found that, for Bcl‐2 and PAX2, an aberrant expression correlated with EIN criteria of premalignancy better than with the WHO criteria, while no significant difference was found for PTEN . Furthermore, in another study we found that the EIN system was more sensitive, but less specific than the WHO one for the risk of cancer coexistent with EH . In these studies, we postulated that a major cause of the difference between WHO and EIN system may lie in the ‘complex non‐atypical EH’ category.…”
Section: Discussionmentioning
confidence: 86%
“…Data were also subdivided into subgroups based on: administration route of progestins (oral or intrauterine), due to the recognized superiority of levonorgestrel‐medicated intrauterine device (LNG‐IUD); histological diagnosis (atypical EH/EEC or non‐atypical EH), since the first two are neoplastic lesions and the latter one is a reactive condition …”
Section: Methodsmentioning
confidence: 99%
“…• histological diagnosis (atypical EH/EEC or non-atypical EH), since the first two are neoplastic lesions and the latter one is a reactive condition. [31][32][33][34] The predictive value of ER and PR was assessed as relative risk (RR)…”
Section: Ta B L E 1 Characteristics Of the Included Studiesmentioning
confidence: 99%
“…4 The EIN system categorizes EH into "benign EH" and "endometrial intraepithelial neoplasia," based on a combination of histomorphologic criteria. 7 To date, histologic examination is the reference standard in differential diagnosis between benign and premalignant EH. 5 On the other hand, the revised 2014 WHO classification has used "atypical EH" and "endometrial intraepithelial neoplasia" as synonyms.…”
Section: Introductionmentioning
confidence: 99%
“…This novel classification categorized EH into three categories: benign EH, EIN without cytologic atypia (at lower risk), and EIN with cytologic atypia (at higher risk). 7 To date, histologic examination is the reference standard in differential diagnosis between benign and premalignant EH. Nonetheless, this method is characterized by poor inter-and intra-observer reproducibility.…”
Section: Introductionmentioning
confidence: 99%